Pengaruh Jarak Tananam Dan Pemberian Pupuk Kandang Terhadap Pertumbuhan Dan Hasil Kacang Tanah (Arachis hypogaea L.) Varietas Hypoma - Rudik Hartanto; Dwi Wahyu Setyaningsih (Universitas Merdeka Madiun, 2021)
Abstractâ€” The present study was aimed at finding out the effect of planting space and manure provision on the growth and yield of peanuts (Arachis hypogaea L.). This study was conducted at Kebun Percobaan of Soerjo Ngawi University, located at a height level of more or less 65 meters above sea level. The temperature was about 20-35 oC. The research was conducted from April to June 2019. This study used a factorial experiment using Random Group Design (RGD) consisting of two factors and 9 combined treatments, repeated 3 times. The first factor was planting space consisting of 3 levels including 10 x 30 cm (J1), 15 x 30 cm (J2), 20 x 30 cm (J3), and manure provision with three levels without fertilization (P0), 5 kg of rumen fertilizer and 10 ml/l (P1) of cow urine, 5 kg of rabbit manure and 10 ml/1 (P2). According to the observation on the effect of space planting on the growth of peanut, planting space of 15 x 30 cm (J2) is considered the best compared to those of 10 x 30 cm (J1) and 20 x 30 cm (J3) as shown in the observation of plant height at 45 days after planting (27.67), the number of leaves (372.07) and the number of branches (8.71). Whereas from the results of the observation of the effect of spacing on peanut yields, the planting space of 20 x 30 cm (J3) is the best compared to those of 10 x 30 cm (J1) and 15 x 30 cm (J2) as shown in the observation of the number of filled peas (21.33). , dry pea weight per plot (1,150) and dry weight of 100 seeds (44.82). The results of the observation of the effect of planting space on peanut yield, the plant spacing of 15 x 30 cm (J2) is superior on dry pea weight per plant (34.89) and the lowest number of empty peas (2.04). The study comes to the conclusion that the effect of manure on the growth of peanut, rabbit manure (p1) which was considered the best among (p0) and (p2) shown in the observation of plant height (45 hst (30.80), number of leaves (367.04) and number of branches (8.82). The observation result of the manure provision effect on the peanuts using cow rumen manure (p2) is considered the best compared to (p0) and (p1) shown in the observation on the number of filled peas (20.77), dry weight per plot (1,260) and weight of 100 seeds (44.64). Â Keywordsâ€”: planting space; manure; growth; peanut; yield.